Combined Phosphorus Limitation and Light Stress Prevent Viral Proliferation in the Phytoplankton Species Phaeocystis globosa, but Not in Micromonas pusilla - Maat, Douwe S.; de Blok, Reinhoud; Brussaard, Corina P. D. (Frontiers in Marine Science, 2016)
Under natural conditions phytoplankton are often simultaneously subjected to phosphorus (P) limitation and suboptimal light levels. Potential interacting effects of P-limitation and light availability on phytoplankton virus-host interactions have thus far not been reported. We studied the influence of three environmentally relevant light levels (low; 25, medium; 100 and high; 250 µmol quanta m-2 s-1) in combination with P-limitation (vs. P-replete conditions) on virus proliferation in the key phytoplankton species Micromonas pusilla and Phaeocystis globosa. Cultures were acclimated to balanced P-limited growth at 3 light levels by semi-continuous culturing, before one-step infection experiments were carried out in batch mode. Under optimal conditions (medium light, P-replete), the latent period (time until first release of progeny viruses) was 6-9 h and 9-12 h, and the burst size (number of viruses released per lysed host cell) was 241±5 and 690±28 for M. pusilla virus MpV and P. globosa virus PgV, respectively. Low light intensity under P-replete conditions prolonged the latent period of PgV (with maximally 3 h). The PgV burst size was 2.8-fold reduced under low light and 2.2-fold reduced under high light. The 10-fold range in light intensity did not affect viral latent period or burst size in P-replete M. pusilla. However, P-limitation (under optimal light) also led to elongated latent periods (with maximally 3 h compared to P-replete) and the viral burst sizes decreased by 2.7-fold for MpV and 3.5-fold for PgV. Finally, infectivity assays showed that PgV progeny from the P-limited high and low light cultures largely lost their infectivity, reducing their infective burst sizes to only 2-4 infective viruses per lysed host cell. Our study demonstrates that the effects of specific light and P-availability on virus-phytoplankton interaction are not only species specific, but can also strengthen each other’s effects. Relatively small differences in environmental conditions with depth, geography or time have the potential to drastically affect viral infection of phytoplankton, with consequent effects on host species composition and biogeochemical fluxes.